2019
DOI: 10.1136/lupus-2019-000333
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum complement levels and higher gene copy number of complementC4Bare associated with hypertension and effective response to statin therapy in childhood-onset systemic lupus erythematosus (SLE)

Abstract: ObjectiveSystemic lupus erythematosus (SLE) features high frequency of cardiovascular disease (CVD) and fluctuating complement levels. The clinical trial Atherosclerosis Prevention in Pediatric Lupus Erythematosus (APPLE) aimed to evaluate whether atorvastatin treatment reduced the progression of atherosclerosis in 221 patients with childhood-onset SLE (cSLE), using carotid intima media thickness (CIMT) as surrogates. We leveraged APPLE biorepository and trial data to investigate the relationship between compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
4
10
0
Order By: Relevance
“…Recent studies from our laboratory have revealed that in patients with lupus inflammation is more closely linked to C4 than C3 levels (11,12). The current study extends this finding to healthy adolescents.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Recent studies from our laboratory have revealed that in patients with lupus inflammation is more closely linked to C4 than C3 levels (11,12). The current study extends this finding to healthy adolescents.…”
Section: Discussionsupporting
confidence: 82%
“…Among human subjects with antiphospholipid antibodies, those who experienced thromboses had consistently higher C4 and C3 serum protein levels and higher C4B gene copy number than patients who did not experience thrombosis (11). Moreover, pediatric lupus patients who had hypertension have persistently higher serum C4 and C3 protein levels than normotensive patients (12).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, it was indicated that overexpression of RPAIN inhibits the expression of C1q and that C1q was the functional target of RPAIN (27). It was also previously reported that C3 and C4 have diagnostic value for SLE (6,7). In the present study, elevated levels of linc8986 and linc0597 in the plasma of patients with SLE were indicated to be negatively correlated with C3, suggesting that high expression of linc8986 and linc0597 may inhibit the expression of C3.…”
Section: Discussionsupporting
confidence: 72%
“…Lupus nephritis (LN), one of the most serious manifestations of SLE, is the major cause of a large number of SLE-related deaths ( 4 , 5 ). In the internationally recognized SLE classification standard, complement component 3 (C3) and C4 are among the immunological diagnostic items for SLE ( 6 , 7 ). Although plasma levels of C3 and C4 are of certain diagnostic value for SLE, they are not specific diagnostic indicators ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is another report that disease activity was associated with hypertension in SLE patients, which compared with those with and without hypertension. Individuals with hyper tension demonstrated significantly elevated serum levels for C4 and C3 at baseline and serially 24) . These results sug gest that high disease activity at diagnosis could be a pre dictor of hypertension in childhoodonset SLE patients.…”
Section: Discussionmentioning
confidence: 98%